2018
DOI: 10.1016/j.jtumed.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of date fruit consumption on labour and vaginal delivery in Tabuk, KSA

Abstract: Objectives The date fruit has been shown to possess several health benefits. This study aims to determine the effects of date fruit consumption on the onset and progression of labour. Methods A randomised controlled clinical study was conducted on 89 participants to assess the effects of date fruit consumption on the onset and progression of labour. Twenty-six participants consumed date fruits alone, and 32 consumed date fruits followed by drinking of water. Thirty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 8 publications
1
52
1
3
Order By: Relevance
“…We gathered 1531 studies from databases and other hand search sources. Eight of 1531 studies (Eight fulltext papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We gathered 1531 studies from databases and other hand search sources. Eight of 1531 studies (Eight fulltext papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
“…1(According to PRISMA statement). Fore of included studies had used the date palm fruit [33,36,39,40], and one study had used date fruit honey [38]. Descriptions and characteristics of the reviewed studies are shown in Table 1.…”
Section: General Characteristicsmentioning
confidence: 99%
“…We gathered 1531 studies from databases and other hand search sources. Nine of 1531 studies (Nine full-text papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40][41]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
“…The flowchart of searching and inclusion process of studies is shown in Figure 1(According to PRISMA statement). Five of included studies had used the date palm fruit [33,36,[39][40][41], and one study had used date fruit honey [38]. Descriptions and characteristics of the reviewed studies are shown in Table 1 sizes of these studies were 89 to 210 participants.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation